Community-based pathogen-specific incidence of influenza-like illness due to respiratory viruses in South-central Vietnam in 2009–2012: after a pandemic of influenza A viruses - Kensuke Takahashi; Shinya Tsuzuki; Minh Nhat Le; Nguyen Hien Anh; Dang Duc Anh; Koya Ariyoshi; Lay-Myint Yoshida (Tropical Medicine and Health)
Abstract Background Influenza-like illness (ILI) is one of the most common illnesses caused by various respiratory viruses and directly or indirectly incurs high expenses to households. However, the pathogen-specific incidence and health-seeking behaviour in communities have not been well described. Methods A longitudinal cohort study using a self-recorded health calendar among 1000 households was performed in South-central Vietnam from October 2009 to September 2012. Endemic respiratory viruses in the community were monitored using random sampling in public health clinics (polyclinics). The monthly incidence of specific pathogens was calculated using the Bayesian method. Findings Among 5,016 household members, 3,687 ILI episodes were reported during the study period. The incidence rate of ILI was 21.7 (95% confidence interval 21.0–22.4) per 1,000 person-months for all ages and highest in children under 2 years with 71.6 (64.7–81.8) followed by 2–4 years with 71.3 (65.8–78.2). Rhinovirus had the highest incidence with 22.5 among the age under 2 years, followed by adenovirus and respiratory syncytial virus (RSV) with 12.5 and 9.9, respectively. Most young children sought treatment from clinics and hospitals, whereas most schoolchildren and adults sought treatment from drugstores. RSV outbreaks significantly increase the number of healthcare visits among children under 2 years, but not in older age groups. Interpretation Several surges of ILI were attributed by multiple respiratory viruses. Healthcare seeking patterns were varied among pathogens. Highly transmissible viruses, such as rhinovirus and adenovirus, pose the potential risk of the next pandemic.